Top Income Shares in OECD Countries: The Role of Government Ideology and Globalization - Florian Dorn; Christoph Schinke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
This paper investigates how government ideology and globalization are associated with top income shares in 17 OECD countries over the period 1970 to 2014. We use top income shares of the World Wealth and Income Database (WID). Globalization is measured by the KOF index of globalization. Static and dynamic panel model results show that the top income shares increased more under rightwing governments than under leftwing governments. The ideology-induced effect was stronger when globalization proceeded more rapidly. Globalization was positively correlated with income shares of the upper-middle class (P99-P90), but negatively with income shares of the rich (top 1%) in the overall sample. We show that the relationship differs between AngloSaxon countries and other OECD countries. Globalization was more pro-rich in AngloSaxon countries than in other OECD countries. Government ideology does not turn out to have a statistically significant effect on top income shares in Anglo-Saxon countries after the 1980s, whereas ideology-induced differences in the distributional outcomes continued in other OECD countries.
Keywords: D31; D72; F62; H80; N30; 330; Income inequality; top income shares; partisan theory; government ideology; globalization; panel data models; Anglo-Saxon countries